Explanatory hypotheses for Irish trade in manufactured goods in mid 1960s - Farley, Noel J.J. (Economic & Social Studies, 1972)
For the last twenty years, the literature on international trade has contained numerous discussions of the Heckscher-Ohlin hypothesis. In ; a world where all economies use similar technologies and have identical homogeneous production functions of the first degree, and similar demand patterns, where factorreversibility does not exist, where factors are immobile as between economies and where transport costs and government policy do not impede trade; it was presumed that an economy would export commodities in which its most abundant'factors of production were incorporated.
Keywords: Trade; Ireland